Seriously injured urban black men’s perceptions of clinical research participation - Bruce, Marta M. (J Racial Ethn Health Disparities, 2015)
PURPOSE: Black men are uniquely vulnerable in American society and our health care system: they bear a disproportionate burden of injury, yet are underrepresented in clinical research. This study aimed to explore the reasons why urban Black men with serious injuries chose to participate in clinical research and their concerns about research participation. METHODS: This qualitative study was conducted within the context of a larger study focused on psychological effects of serious injury in urban Black men. 83 Black men with serious injuries were recruited while hospitalized in an urban trauma center. Informed consent was obtained. Semi-structured interviews were conducted in participants’ homes three months after discharge from the hospital, and were audiotaped, transcribed, and de-identified. Thematic content analysis was used to identify themes about perceptions of participating in clinical research. RESULTS: The mean age of our sample was 38.2 years, and the mean injury severity score was 10.7 (SD 9.6). The majority (53.2%) of injuries was due to interpersonal violence and 46.8% were due to unintentional mechanisms. Eight reasons for research participation emerged from the data: human connection, altruism/community, self-improvement, compensation, gaining knowledge, curiosity/interest, low risk, and reciprocity. CONCLUSIONS: A major finding was that injured urban Black men participated in clinical research for the opportunity for human and therapeutic connection. Despite some expressions of mistrust, participants were willing to participate for altruistic reasons rooted in community priorities, and as part of their recovery process post-injury.